A Resource‐Based View of the Build/Buy Decision: Emergent and Rational Stepwise Models of Strategic Planning1. (20th January 2016) - Sims, Julian; Powell, Philip; Vidgen, Richard
Abstract : Two ideal models of strategy development are identified: one is rational stepwise; the other is emergent, ex‐post, relying on experimentation where strategy is used to legitimize what has already been accomplished.